Design of Pb(II)-Specific E. coli-Based Biosensors by Engineering Regulatory Proteins and Host Cells - Jeon, Yangwon; Lee, Yejin; Jang, Geupil; Kim, Bong-Gyu; Yoon, Youngdae (Frontiers in Microbiology, 2022)
Bacterial cell-based biosensors have been widely developed for detecting environmental toxic materials. The znt-operon in Escherichia coli is a Zn(II)-responsive genetic system and is employed in Zn(II), Cd(II), and Hg(II)-sensing biosensors. In this study, point mutations were introduced in the regulatory protein ZntR to modulate its target selectivity, and metal ion-exporting genes, such as copA and zntA, in host cells were deleted to increase cellular metal ion levels and enhance specificity. Thus, the overall responses of the E. coli cell-based biosensors toward metal(loid) ions were increased, and their selectivity, which was originally for Cd(II) and Hg(II), was shifted to Pb(II). The gene encoding ZntA, known as the Zn(II)-translocating P-type ATPase, showed impact on the ability of E. coli to export Pb(II), whereas copA deletion showed no significant impact. Noteworthily, the newly generated biosensors employing ZntR Cys115Ile showed capacity to detect under 5 nM Pb(II) in solution, without response to other tested metal ions within 0–100 nM. To understand the marked effect of single point mutations on ZntR, computational modeling was employed. Although it did not provide clear answers, changes in the sequences of the metal-binding loops of ZntR modulated its transcriptional strength and target selectivity. In summary, the approaches proposed in this study can be valuable to generate new target-sensing biosensors with superior selectivity and specificity, which can in turn broaden the applicability of cell-based biosensors to monitor Pb(II) in environmental systems.